Тайны Баден-Бадена - Вербинина Валерия (Любовь, интрига, тайна, 2017)
Экземпляры: аб. (2018) / Инвентарный номер: 54518 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 31 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6